(untitled) (Revista Científica Integrada, 2025)
Objective: To develop a molecular docking study with the enzyme phospholipase A2 (PLA2) in the presence of compounds analogous to p-bromofenacil bromide with a view to drug repositioning. Methods: The tertiary structure of the target protein from Agkistrodon halys pallas (Viperidae) was obtained from the RCSB PDB database, and the ligands obtained from the PubChem website were 4,4’-dibromobenzyl and 2-bromopropiophenone. After refining the molecules, molecular docking analyses were carried out to evaluate the Gibbs free energy, the distances between atoms, and types of bonds in the active site. Results: The compound 4,4’-dibromobenzyl was found to be related to the active site residue Tyr 52 through hydrophobic interactions. Regarding the compound 2-bromopropiophenone, a hydrophobic interaction with the active site residue Tyr 52 and a hydrogen bond with the residue Gly 32 were observed. Other amino acid residues (Gly 32 and Asp 49) located close to the catalysis region presented hydrophobic interactions. Conclusions: Although the ligand atoms are close to the enzyme’s catalytic site, they exhibit hydrophobic interactions and hydrogen bonding. In vitro and in vivo studies are needed to corroborate the theoretical results.